2018
DOI: 10.25077/jka.v7.i3.p400-404.2018
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Aktivitas Fisik dengan Kadar Glukosa Darah Puasa pada Pasien Diabetes Melitus yang Datang ke Poli Klinik Penyakit Dalam Rumah Sakit M. Djamil Padang

Abstract: AbstrakAktivitas fisik merupakan satu dari empat pilar program penatalaksanaan diabetes mellitus. Aktivitas fisik yang kurang juga merupakan salah satu penyebab meningkatnya angka kejadian diabetes melitus. Tujuan penelitian ini adalah menentukan hubungan aktivitas fisik dengan kadar glukosa darah puasa pada pasien diabetes melitus. Jenis penelitian ini adalah analitik dengan pendekatan potong lintang terhadap 120 pasien diabetes melitus yang datang ke poliklinik penyakit dalam rumah sakit Dr. M. Jamil Padang … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 0 publications
0
3
1
10
Order By: Relevance
“…According to Plotnikoff (2006, in Mala Azitha, 2018, physical activity is the key in managing diabetes mellitus, especially as a controll of blood sugar, such as reducing hyperinsulinemia, increasing insulin sensitivity, lowering body fat, and lowering blood pressure. [10] Statistical test results showed that there was no relationship between physical activity and cholesterol levels (p = 0.758). This is not in line with research from Sumosardjuno (2007 in Ayu Candra, 2017) which states that people who use a lot of physical activity in daily life can increase HDL level in the blood thereby improving coronary collateral so that CHD risk can be reduced [11].…”
Section: Resultsmentioning
confidence: 95%
“…According to Plotnikoff (2006, in Mala Azitha, 2018, physical activity is the key in managing diabetes mellitus, especially as a controll of blood sugar, such as reducing hyperinsulinemia, increasing insulin sensitivity, lowering body fat, and lowering blood pressure. [10] Statistical test results showed that there was no relationship between physical activity and cholesterol levels (p = 0.758). This is not in line with research from Sumosardjuno (2007 in Ayu Candra, 2017) which states that people who use a lot of physical activity in daily life can increase HDL level in the blood thereby improving coronary collateral so that CHD risk can be reduced [11].…”
Section: Resultsmentioning
confidence: 95%
“…The variables used are those previously researched variables, such as that of Adnan et al [9] analyzing the correlation between IMT with blood glucose of diabetics, and that of Nurayanti and Adriani [10], and Azitha et al, the three of which analyzed the correlation between physical activities and blood glucose [11]. However, the risk of losing some nutrients on diabetics, especially micro nutrients must also be taken into consideration.…”
Section: Methodsmentioning
confidence: 99%
“…Ketika tubuh melakukan aktivitas fisik, akan terjadi peningkatan kebutuhan bahan bakar tubuh oleh otot yang aktif dan juga adanya reaksi tubuh yang kompleks meliputi fungsi sirkulasi metabolisme, pelepasan dan pengaturan hormonal dan susunan saraf otonom. Diharapkan dengan dijadikannya glukosa sebagai bahan bakar utama, kadar glukosa darah akan menurun (Azitha, Aprilia, & Ilhami, 2018). Aktivitas fisik yang dapat dilakukan oleh anggota Prolanis adalah seperti jalan kaki, bersepeda, senam diabet, maupun naik turun tangga.…”
Section: Pendahuluanunclassified